2010
DOI: 10.1523/jneurosci.5252-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Electric Stimulation Entrains Cortical Neuronal Populations in Rats

Abstract: Low intensity electric fields have been suggested to affect the ongoing neuronal activity in vitro and in human studies. However, the physiological mechanism of how weak electrical fields affect and interact with intact brain activity is not well understood. We performed in vivo extracellular and intracellular recordings from the neocortex and hippocampus of anesthetized rats and extracellular recordings in behaving rats. Electric fields were generated by sinusoid patterns at slow frequency (0.8, 1.25 or 1.7 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
352
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 368 publications
(379 citation statements)
references
References 78 publications
(124 reference statements)
18
352
1
Order By: Relevance
“…A minimum threshold of 1 mV/mm has been suggested on the basis of in vivo measurements in rodents (17). Electric fields measured in vivo in humans fall within this range; however, rather at the lower end.…”
Section: Discussionmentioning
confidence: 95%
“…A minimum threshold of 1 mV/mm has been suggested on the basis of in vivo measurements in rodents (17). Electric fields measured in vivo in humans fall within this range; however, rather at the lower end.…”
Section: Discussionmentioning
confidence: 95%
“…Recently several studies have reported that endogenous electric fields provide an effective (and maybe indispensable) mechanism for a rapid orchestration of neocortical spatiotemporal synchronization patterns (e.g., Anastassiou et al, , 2011Fröhlich and MecCormick, 2010;Marshall et al, 2006;Ozen et al, 2010;Radman and Nicholson, 2007;Weiss and Paulsen, 2010). Although the magnitude of local fields is considerably lower than the typical threshold potential of a neuron Fröhlich and MecCormick, 2010) they still may modulate spike timing of single neurons via ephaptic coupling (Radman and Nicholson, 2007) as well as the collective neuronal dynamics of entire neuronal populations (Fröhlich and MecCormick, 2010;Weiss and Paulsen, 2010).…”
Section: Volume Conduction and Choice Of Referencementioning
confidence: 99%
“…Although the magnitude of local fields is considerably lower than the typical threshold potential of a neuron Fröhlich and MecCormick, 2010) they still may modulate spike timing of single neurons via ephaptic coupling (Radman and Nicholson, 2007) as well as the collective neuronal dynamics of entire neuronal populations (Fröhlich and MecCormick, 2010;Weiss and Paulsen, 2010). Endogenous local fields modulate neuronal membrane potentials on a subthreshold level (Fröh-lich and MecCormick, 2010;Ozen et al, 2010;Weiss and Paulsen, 2010) and thereby influence network activity. In this way, a feedback loop may be established (Fröhlich and MecCormick, 2010), which may promote global synchronization of large neuronal assemblies.…”
Section: Volume Conduction and Choice Of Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Its application involves inducing a weak electric current between electrodes at the scalp (Nitsche et al 2008;Zaghi et al 2010;Paulus 2011). The current partially penetrates the brain, where it propagates widely and forces neuronal excitability to oscillate along with its alternating waveform (Frohlich and McCormick 2010;Ozen et al 2010).…”
Section: What Is Tacs?mentioning
confidence: 99%